The Concept of Boycott and Its Relevance to QS. Al-Ma'idah/5:2 from the Perspective of Tafsir Al-Azhar by Buya Hamka - Elpi Dayanti Siregar; Muhammad Hidayat (Journal of Indonesian Islamic Studies, 2026)
This study aims to analyze the concept of boycott and its relevance to Qur’an Surah Al-Mā’idah (5):2 from the perspective of Tafsir Al-Azhar by Buya Hamka. The study employed a qualitative approach using library research. The primary data consisted of Qur’an Surah Al-Mā’idah (5):2 and Tafsir Al-Azhar, while secondary data were obtained from books, journal articles, and other relevant literature. Data were collected through documentation and analyzed using content analysis and descriptive-interpretative analysis. The findings indicate that Qur’an Surah Al-Mā’idah (5):2 contains a command to cooperate in righteousness and piety and a prohibition against cooperation in sin and hostility. From Hamka’s perspective, these principles encompass both social relations and economic activities. A boycott may be understood as a form of moral responsibility and humanitarian solidarity when it seeks to reduce support for injustice, is conducted peacefully, is based on valid information, and takes public benefit into consideration. This study emphasizes that boycott is not merely an economic action but also has ethical, social, and spiritual dimensions. The novelty of this study lies in integrating the concept of boycott, the principle of ta‘āwun (mutual cooperation), and the perspective of Tafsir Al-Azhar as a framework for contemporary boycott ethics.